The Influence Of Problem Based Learning Model Accompanied By Multirepresentation Based Students Worksheets on Junior High School Students Learning Outcomes - Arifin, Ahmad Zainul; Mahardika, I Ketut; Budiarso, Aris Singgih (Peneliti.net, 2024)
This research was conducted to test the significant influence of using the problem-based learning model accompanied by multi-representation-based students worksheets (LKPD) on junior high school students' learning outcomes. The research method used was quasi-experimental with a nonequivalent control group design. The research subjects were class VIII students at SMP Katolik Santo Petrus Jember in the even semester of the 2022/2023 academic year, with 52 students divided into experimental and control classes. Data collection uses test techniques in the form of pretest and posttest accompanied by data analysis techniques in the form of normality test, independent sample t-test, and right-tailed t-test. The results of the research show that the use of the problem-based learning model accompanied by multi-representation-based students worksheets (LKPD) for junior high school students has a significant effect on improving the learning outcomes of junior high school students.